Investigating the effects of cooling rate on distortion of asymmetric composite laminates. (15th March 2020) - Mobarakian, Mohsen; Safarabadi, Majid; Farahani, Mohammadreza
Abstract: Predicting the final shape of composite laminates after the curing cycles is crucial. An experimental and two numerical (with constant and temperature dependent material properties) studies have been presented. The purpose of this study is to investigate the effects of different cooling rates on the distortion of thin asymmetric composite laminates with different lay-ups after the curing cycle. Properties of a UD layer in different temperature have been obtained using TMA, DMA and micromechanical formulation. The samples were subjected to three different cooling stages. Results indicated that the distortion of the asymmetric composite laminate was significantly depending on the cooling rate and lay-up configurations. Accelerating the cooling rate can significantly enhance the out of plane deformation of the asymmetric laminates. In the slowest cooling rate, the effects of thermal residual stresses due to temperature change are minimum and consequently the results of both numerical analyses are closer to experimental observations. The analysis with temperature dependent material can predict the deformation of specimens with slowest cooling rate better than the analysis with constant material properties. Because of the sudden change in temperature, for prediction of distortion after the higher cooling rates, a transient analysis will be needed.